KEMAMPUAN PEMECAHAN MASALAH ANAK USIA 5-6 TAHUN DALAM PEMBELAJARAN STEAM BERBASIS PROJEK KINCIR ANGIN DI TK GUDISEJU T.A. 2025/2026 - Putri Indah Sari Sidauruk; Peny Husna Handayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to determine the differences in problem-solving abilities of children aged 5–6 years before and after participating in STEAM-based windmill project learning at TK Gudiseju in the 2025/2026 academic year. The study was motivated by the low level of children’s problem-solving abilities, which was reflected in their limited initiative to observe, ask questions, try solutions, and communicate their ideas independently. STEAM-based project learning was chosen because it provides contextual, active, and meaningful learning experiences through exploration and simple experiments. This research employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The sample consisted of 13 children in Group B at TK Gudiseju selected through saturated sampling techniques. Data were collected through observation using an early childhood problem-solving ability observation sheet. The treatment was carried out through STEAM-based windmill project learning activities conducted in three meetings. Data were analyzed using the Wilcoxon Signed Rank Test. The results showed a significant difference in children’s problem-solving abilities before and after the implementation of STEAM-based windmill project learning. Children’s abilities improved in observing problems, asking questions, trying solutions, classifying information, and communicating activity results. Therefore, STEAM-based windmill project learning was proven effective in improving the problem-solving abilities of children aged 5–6 years